Role of Cdkn2a in the Emery–Dreifuss Muscular Dystrophy Cardiac Phenotype - Gloria Pegoli; Marika Milan; Pierluigi Giuseppe Manti; Andrea Bianchi; Federica Lucini; Philina Santarelli; Claudia Bearzi; Roberto Rizzi; Chiara Lanzuolo (Biomolecules, 2021)
The Cdkn2a locus is one of the most studied tumor suppressor loci in the context of several cancer types. However, in the last years, its expression has also been linked to terminal differentiation and the activation of the senescence program in different cellular subtypes. Knock-out (KO) of the entire locus enhances the capability of stem cells to proliferate in some tissues and respond to severe physiological and non-physiological damages in different organs, including the heart. Emery–Dreifuss muscular dystrophy (EDMD) is characterized by severe contractures and muscle loss at the level of skeletal muscles of the elbows, ankles and neck, and by dilated cardiomyopathy. We have recently demonstrated, using the LMNA Δ8–11 murine model of Emery–Dreifuss muscular dystrophy (EDMD), that dystrophic muscle stem cells prematurely express non-lineage-specific genes early on during postnatal growth, leading to rapid exhaustion of the muscle stem cell pool. Knock-out of the Cdkn2a locus in EDMD dystrophic mice partially restores muscle stem cell properties. In the present study, we describe the cardiac phenotype of the LMNA Δ8–11 mouse model and functionally characterize the effects of KO of the Cdkn2a locus on heart functions and life expectancy.